Dvouleté výsledky léčby vlhké formy věkem podmíněné makulární degenerace s použitím léků proti vaskulárnímu endotelovému růstovému faktoru - Studnička, J; Rencová, E; Dusová, J; Marák, J; Burova, M; Rozsíval, P; Jarkovský, J; Kandrnal, V (Ceska a slovenska oftalmologie, 2013)
AIM: The aim of the study was to establish the efficacy of anti VEGF (Vascular Endothelial Growing Factor) drugs in the treatment of wet form ARMD (Age-Related Macular Degeneration) in everyday clinical practice in the Department of Ophthalmology, Faculty Hospital, Hradec Králové, Czech Republic, E.U., in patients registered in the Czech national registry AMADEUS. MATERIAL AND METHODS: Retrospective study with 24 months follow-up period. In the group were evaluated 143 eyes of 140 patients, out of them were 77 women (65.8 %), of average age 73.09 (71.69 - 74.48) years, and 40 men (34.2 %) of average age 74 (58 - 85) years. All of the patients were completely examined before the beginning of the treatment; during the treatment were, except the standardized eye examination, in patients treated with ranibizumab the color fundus photography and Optical Coherence Tomography (OCT) with measuring of the central retinal thickness performed every three months at least. The patients treated by pegaptanib were examined every six weeks before the drug application. The fluorescence angiography (FA) was performed at the beginning of the treatment to establish the type and extension of the choroidal neovascularization and during the treatment in case of necessity to establish the activity of the choroidal neovascular membrane (CNV). The treatment by ranibizumab was in the regimen PRN (pro re nata), and pegaptanib was applied every six months during the first year with the follow-up evaluation of the findings. The treatment evaluations were performed at 12 and 24 months. RESULTS: During the two years follow - up period, the authors noticed in patients treated with ranibizumab loss of 5.12 letters of ETDRS optotypes in case of mostly classical CNV, in occult CNV loss of 5.45 letters, and in minimally classical CNV loss of 2.83 letters. In three evaluated eyes with classical CNV in patients treated with pegaptanib we noticed after 2 years loss of 6.67 letters, in eleven eyes with occult CNV we established loss of 9.91 letters, and in two eyes with minimally classical CNV the average best-corrected visual acuity (BCVA) remained unchanged. The pegaptanib treatment results may be influenced by small number of evaluated patients. The visual acuity changes during the two years treatment were not statistically significant. We noticed the decrease of average CRT (central retinal thickness) in all types of CNV treated both with ranibizumab and pegaptanib after the two years follow up. To reach these results, an average of 5.51 applications of ranibizumab and 9 applications of pegaptanib during the two years were used. CONCLUSION: In the followed-up group we found, comparing to the natural course of neovascular form of ARMD, retarding of the BCVA decrease during the two years treatment with VEGF inhibitors in everyday clinical practice. Better results were achieved with ranibizumab treatment, however the differences were not statistically significant. Key words: age related macular degeneration, AMADEUS Czech national registry, ranibizumab, pegaptanib.
Keywords: rozvrh dávkování léků; Wet Macular Degeneration; Tomography, Optical Coherence; Female; aptamery nukleotidové; výsledek terapie; ženské pohlaví; Aptamers, Nucleotide; vaskulární endoteliální růstový faktor A; optická koherentní tomografie; lidé; bevacizumab; fundus oculi; Angiogenesis Inhibitors; inhibitory angiogeneze; Drug Administration Schedule; Vascular Endothelial Growth Factor A; Treatment Outcome; Aged, 80 and over; následné studie; Fluorescein Angiography; Fundus Oculi; vlhká makulární degenerace; retrospektivní studie; Follow-Up Studies; Male; Bevacizumab; Aged; fluoresceinová angiografie; ranibizumab; lidé středního věku; humanizované monoklonální protilátky; senioři nad 80 let; senioři; mužské pohlaví; Antibodies, Monoclonal, Humanized; zraková ostrost; Ranibizumab; Visual Acuity; Retrospective Studies; Middle Aged; Humans